Nyāsa-paryālocana : Jinendrabuddhikrta Kāśikāvivaraṇapañjikā kā ȧlocanātmaka adhyayana - Śāstrī, Bhīmasena, 1920- (Bhīmasena Śāstrī : prāpti-sthāna, Bhaimī Prakāśana, 1979)
Critical study of Jinendrabuddhi's Nyāsa, 8th century commentary on Vāmana and Jayāditya's Kāśikā, 7th century commentary on Pāṇini's Aṣṭādhyāyī, aphoristic work on Sanskrit grammar.